Structural brain MRI studies in eye diseases: are they clinically relevant? A review of current findings. (11th September 2015) - Prins, Doety; Hanekamp, Sandra; Cornelissen, Frans W.
Abstract: Many eye diseases reduce visual acuity or are associated with visual field defects. Because of the well‐defined retinotopic organization of the connections of the visual pathways, this may affect specific parts of the visual pathways and cortex, as a result of either deprivation or transsynaptic degeneration. For this reason, over the past several years, numerous structural magnetic resonance imaging (MRI) studies have examined the association of eye diseases with pathway and brain changes. Here, we review structural MRI studies performed in human patients with the eye diseases albinism, amblyopia, hereditary retinal dystrophies, age‐related macular degeneration (AMD) and glaucoma. We focus on two main questions. First, what have these studies revealed? Second, what is the potential clinical relevance of their findings? We find that all the aforementioned eye diseases are indeed associated with structural changes in the visual pathways and brain. As such changes have been described in very different eye diseases, in our view the most parsimonious explanation is that these are caused by the loss of visual input and the subsequent deprivation of the visual pathways and brain regions, rather than by transsynaptic degeneration. Moreover, and of clinical relevance, for some of the diseases – in particular glaucoma and AMD – present results are compatible with the view that the eye disease is part of a more general neurological or neurodegenerative disorder that also affects the brain. Finally, establishing structural changes of the visual pathways has been relevant in the context of new therapeutic strategies to restore retinal function: it implies that restoring retinal function may not suffice to also effectively restore vision. Future structural MRI studies can contribute to (i) further establish relationships between ocular and neurological neurodegenerative disorders, (ii) investigate whether brain degeneration in eye diseases is reversible, (iii) evaluate the use of neuroprotective medication in ocular disease, (iv) determine optimal timing for retinal implant insertion and (v) establish structural MRI examination as a diagnostic tool in ophthalmology.